ANALISIS PAJAK PENGHASILAN PASAL 21, 23, 25 PT MBC TAHUN 2020 - Denisa Chrissiera; Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2023)
This research aims to find out whether the deduction, deposit and reporting of Income Tax Article 21, Article 23 and Article 25 of PT MBC has been in accordance with the provisions of the Tax Regulation applicable in Indonesia. Data collection techniques are obtained through in-field research, interviews, documentation, literature studies. The type of research used is qualitative research with descriptive methods. The results of this study showed that the withholding and reporting of income tax article 21, article 23, and article 25 conducted by PT MBC was in accordance with the applicable tax provisions. In terms of the compliance of taxpayers from depositing and reporting, PT MBC has delays and corrections in the deposit and reporting of Income Tax Article 21 and Article 23. In Income Tax Article 25 there is no delay and has been in accordance with KEP-537 / PJ / 2000.